(untitled) (European journal of volunteering and community-based projects, 2024)
Purpose. This paper systematically reviews the current literature on Greenwashing, aiming to organize existing knowledge on the phenomenon. The research investigates and categorizes the main sub-topics within the broader realm of greenwashing, providing deeper insights and suggesting areas for future research. Design/methodology/approach. Employing a qualitative design and Latent Dirichlet Allocation (LDA) analysis, a systematic literature review has been conducted, analyzing a dataset of 1,846 original contributions. Findings. The analysis identified six sub-topics of greenwashing and three macro-categories: 1) Business-related effects, such as impacts on business credibility and brand; 2) Consumer-related effects, including implications for human rights and consumptions; and 3) Social-related effects, encompassing greenwashing regulation and its relationship with Corporate Social Responsibility. The study concludes by discussing implications for consumers, managers, and policymakers. Originality/value. Unlike previous systematic reviews of Greenwashing concept, this study focuses on establishing a comprehensive and holistic framework of the main aspects within this field of research, rather than analyzing just specific sub-elements.